Business–IT Strategic Alignment as a Driver of Integrated E-Service Delivery in Public Institutions: A PLS-SEM Approach - Ayoub M Mswahili; Simon S Msanjila; Fridric Chali (Universitas Komputer Indonesia, 2026)
This study investigates organisational and technological factors influencing Business–IT Strategic Alignment (BITSA) towards designing and implementation of integrated e-service delivery within public institutions, addressing the persistent challenge of siloed, non-interoperable platforms that undermine citizen-centric digital transformation. Grounded in the Strategic Alignment Model (SAM), a cross-sectional survey of 411 respondents from 16 Tanzanian public institutions was conducted, with data analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test relationships between alignment constructs and integrated e-service outcomes. The findings reveal that BITSA is a significant positive predictor of integrated e-service delivery (β = 0.196, p < .001), with IT Strategy–Infrastructure/Processes Alignment (β = 0.265, p < .001), Strategic Performance Measures Alignment (β = 0.153, p = .002), and IT–Business Functional Alignment (β = 0.093, p = .047) emerging as key drivers. Conversely, E-services Strategic Collaboration, Communication, and Business Infrastructure Alignment exerted negative effects, reflecting coordination difficulties and structural rigidities. The model explains a moderate portion of the variance in BITSA (R² = 16.9%) but only a small share in integrated e-service delivery (R² = 3.8%). This study extends alignment theory to the public sector by empirically demonstrating BITSA’s enabling role in integrated e-services, while highlighting that successful integration requires enhanced cross-agency collaboration, organisational flexibility, and supportive policies and leadership. Practically, the findings underscore the need for governments to complement technical competence with strategic leadership, collaborative governance, and policy frameworks to achieve sustainable e-service integration.